(untitled) (Social and Environmental Law Journal, 2024)
This article aims to analyze and reflect about the paradigmatic importance of the Advisory Opinion nº 23/2017 to the recognition within the scope of the Inter-American Convention on Human Rights and the judicialization towards the Inter-American Court on Human Rights. The study goal identified the principle innovation came through the advisory opinion, in addition to the jurisprudential aspects developed about the healthy environment theme in face of the Inter-American Court. The methodology adopted is deductive through the qualitative bibliographic research from books, articles related with subjects, beyond the legislative and jurisprudential research. In this regard, it has been completed through the analysis of the sentence from the case Indigenous Communities la Associación Lhaka Honhat (Nuestra Tierra) vs. Argentina Case, the rise of the OC-23/17 impacts the judgment of healthy environment cases in the American Human Rights Convention.